Simultaneous Determination of 5 Flavonoids and 7 Saponins for Quality Control of Traditional Chinese Medicine Preparation Xinnaoshutong Capsule Using HPLC-VWD-ELSD. (16th January 2017) - Li, Jin; Bai, Yang; Zhang, Peng; He, Jun; Cao, Jun; An, Mingrui; Hu, Li-min; Gao, Xiu-mei; Chang, Yan-xu
Abstract : Xinnaoshutong capsule (XC) is a traditional Chinese prescription derived from the ripe fruit of Tribulus terrestris L. (TT). Although XC has long been considered as an important herbal medicine, no analytical method of marker compounds for quality assessment is registered in the Chinese Pharmacopoeia. A simple analytical method of twelve marker components was developed and validated by HPLC-VWD-ELSD method. Chromatographic separation by HPLC was carried out on a Hedera ODS 2 column (4.6 × 250 mm, 5 μ m) by gradient elution with acetonitrile-water (0.1% formic acid) as the mobile phase. Various extraction conditions were optimized to achieve twelve marker compounds with faster extraction and higher recovery. The analytical condition was then validated in terms of the linearity, accuracy and precision, repeatability, and stability. The twelve markers were successfully quantified in 30 batches of commercial samples. The developed HPLC-VWD-ELSD could be used as a rapid and reliable way in the assessment and quality control of XC and TT.